REUSE OF SPUN PILE PRODUCTION WASTE FOR PAVING BLOCK DEVELOPMENT BY TAGUCHI METHOD - Wajdi, Farid; Herkuntarto, Fajar; Ramayanti, Gina (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
The production of precast spun piles generates solid and liquid waste products. The solid waste consists of stone, sand, and mud materials, while the liquid waste consists of K-600 grade concrete cement mixed with water. It is poured into a 1m3 container and solidifies within 3 hours. The production process of precast concrete piles is fast, which results in quick waste accumulation in the factory area. This research aims to transform the waste into paving blocks suitable for road construction. The Taguchi method is employed to determine the optimal strength of the paving blocks using three variables: (1) the ratio of solid to liquid waste in three levels - 70:30%, 60:40%, and 50:50%, (2) mixing time in three levels - 5, 10, and 15 minutes, and (3) curing time in three levels - 3, 7, and 14 days. The strength of the paving blocks is tested by measuring the maximum compressive strength. The results indicated that the best combination for achieving maximum compressive strength was using (1) a 50%:50% ratio of solid to liquid waste, (2) a curing time of 14 days, and (3) a mixing time of 5 minutes, resulting in a maximum compressive strength of 125.72 Kg/cm2. It is equivalent to Grade D paving blocks that are suitable for road application.